A Synthetic test of rhythm - Jayanthi Ray (Journal of All India Institute of Speech and Hearing)
Suprasegmentals are properties of speech that have a domain larger than a single element. For being analogous to, superficial decoration, suprasegmentals or prosody consisting of stress, rhythm, intonation & juncture, functions as the foundation or structural support for the organisation of speech communication. Of these, rhythm is intrinsic & critical in both production & perception of speech. Several studies have been conducted in the past to gain a knowledge of the development of speech rhythm in children. However, this topic is not yet understood & there is a pressing need to conduct research in this area, in order to use it clinically. In this context the present study was aimed to highlight the developmental trend of rhythm in children & develop a synthetic test of rhythm.